Measuring antibiotic prescribing in hospitalised children in resource‐poor countries: A systematic review. Issue 3 (17th June 2011) - Irwin, Adam; Sharland, Mike
Abstract Antibiotic resistance represents a significant threat to global health. Widespread exposure to antibiotics drives the development of antibiotic resistance. Little is known about the exposure to antibiotics of hospitalised children, particularly in resource‐poor countries where the burden of infectious disease is highest. The review sought to identify original research quantifying antibiotic use in hospitalised children in resource countries. The methods used were: A systematic search of the MEDLINE, CINAHL, EMBASE, LILACS and African Index Medicus databases. Eighteen papers were identified and the methodology varied considerably. Only seven used a recognised defined daily dose (DDD) methodology. The studies reveal a high exposure of hospitalised children to antibiotics. With the exception of data from China, the studies were limited by their design. Limited evidence of the variation in drug, dose and total exposure to antibiotic use in hospitalised children in resource‐poor countries exists. An international network of surveillance of both antimicrobial prescribing and resistance using a simple standardised methodology in this context remains an important goal. A simplified paediatric version of the adult DDD methodology is required to allow international comparison between populations.